The Influence of Servant Leadership and Work Environment on Employee Performance in Family Business UD. Berkat Bersama With Work Motivation as a Mediator - Dewi Sinta (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
This study aims to determine the effect of servant leadership leadership style and work environment on employee motivation and its impact on employee performance. The variables used in this study are servant leadership style and work environment as independent variables, work motivation as a mediating variable and employee performance as the dependent variable. The method used is quantitative mediation. The sample used in this study used a non-probability sampling method with a saturated sample technique and a sample of 50 respondents. Data collection techniques in this study were carried out by distributing questionnaires using a Likert scale. Based on the results of data analysis, it can be concluded that the servant leadership style has a significant effect on work motivation, the servant leadership leadership style has a significant effect on employee performance, the work environment has a significant effect on work motivation, the work environment has a significant effect on employee performance, and work motivation has a significant effect on performance. employee.